2012
DOI: 10.7314/apjcp.2012.13.4.1495
|View full text |Cite
|
Sign up to set email alerts
|

Factors Related to Self-perception of Diet Quality among South Korean Adults

Abstract: Objective: Improvements in diet can decrease the cancer rates. The aim of the present study was to determine the relationships between self-perception of diet quality and personality, impulsiveness, stress, coping strategy, sense of coherence, self-efficacy, and social support. Methods: This cross-sectional study was conducted using a multiple-stratified random sampling method based on the Korea Census of 2007. In October 2009, investigators conducted 15-minute face-to-face interviews with 1,530 South Korean v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 76 publications
(84 reference statements)
0
6
0
Order By: Relevance
“…Association between self-perception of diet and health and food outcomes has been reported in other noteworthy studies in the literature. 14,[19][20][21] Self-perception of diet can therefore be a simple and feasible means of inferring the quality of a person's diet. 4,22 Females had lower positive perception of diet than males.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Association between self-perception of diet and health and food outcomes has been reported in other noteworthy studies in the literature. 14,[19][20][21] Self-perception of diet can therefore be a simple and feasible means of inferring the quality of a person's diet. 4,22 Females had lower positive perception of diet than males.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that older people demonstrate greater variety in food intake. 6,8,14,20 The elderly may also restrict intake of some types of food, as a preventive or treatment measure in the face of chronic diseases and, as a consequence of this attitude, may consider their diet to be healthier. 8,14 In our study, schooling did not show any statistical difference with perception of diet.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with a higher income were more likely to perceive unhealthy diet as a cause of cancer. Kye et al [ 25 ] revealed that respondents with a higher income consumed a healthy diet more often. Also, people who lived in a small-medium–sized city or rural area where manual labor that requires heavy work was common were more likely to perceive physical inactivity as a cause of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, factors such as age, marital status, family income, sex, stress level and physical exercise influence this self-perception. 3,4 Older individuals with lower stress level and who regularly practice physical exercises, as well as those who live with a partner, tend to better assess their food intake, compared to younger individuals, with higher stress levels, sedentary habits and who live alone. 3,4 The impact of family income on the selfperception of dietary quality was clearly demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Older individuals with lower stress level and who regularly practice physical exercises, as well as those who live with a partner, tend to better assess their food intake, compared to younger individuals, with higher stress levels, sedentary habits and who live alone. 3,4 The impact of family income on the selfperception of dietary quality was clearly demonstrated. In a study conducted in the United States the individuals who rated their nutrition as excellent had a family income significantly higher than that of the individuals who rated their nutrition as poor, despite the little difference in spending with food between the two groups.…”
Section: Introductionmentioning
confidence: 99%